Investigate Teacher's Strategy for Teaching Speaking in Classroom and Students' Responses - purnama, yova ananda; Srisudarso, Mansyur; Wahyuna, Yuna Tresna (Peneliti.net, 2024)
This research aims to investigate the strategies employed by teacher’s in teaching speaking and to find out students respon while learning with this strategy. This investigation involves an English teacher and 11th-grade students from a high school in Jakarta. The research employs classroom observations and interviews to gather the necessary data. The findings of this study reveal that teachers utilize strategy such as role-playing, small-group discussions, and storytelling to teach speaking skills. When deciding on a teaching strategy, teachers first consider the specific characteristics of their students. Additionally, three common challenges were identified in students' speaking skills development: limited vocabulary proficiency, pronunciation issues, and a lack of self-assurance. Remarkably, the study indicates that students exhibited favorable reactions to the teacher's instructional strategies.